Innovative Strategies for Memorizing the Qur'an at SLB IT Sahabat Al-Qur'an Binjai - Sarmila Astina Batubara; Ali Darta (al-Afkar, Journal For Islamic Studies, 2025)
The phenomenon of children with disabilities being able to memorize the Qur’an demonstrates remarkable potential, despite facing dominant challenges such as impairments in sensory, physical, rational, and mental functions. SLB IT Sahabat Al-Qur’an Binjai is one of the educational institutions specifically designed to facilitate Qur’an memorization for children with disabilities. This study aims to explore innovative strategies for Qur’an memorization learning at SLB IT Sahabat Al-Qur’an Binjai, addressing the challenges and providing effective solutions for students with special needs. This research employs a qualitative field study approach, utilizing data collection techniques such as observation, interviews, and documentation, supported by literature review. The findings reveal that the learning strategies implemented include the talaqqi method, multisensory approaches, and various creative and engaging methods. These strategies have proven effective in helping students achieve memorization goals, although teaching and learning challenges persist. This study recommends the provision of more inclusive learning media and facilities to support the development of advanced methods in response to emerging educational challenges.